Arkeologi Sejarah Islam di Pesisir Selatan Pulau Seram Maluku Tengah - Wuri Handoko (Balai Arkeologi Maluku, 2016)
The history of Islamization in the region Seram Island Maluku until recently only records the Kingdom Hoamoal as the center of Islamization in the region. However, the formation of customary lands inhabited by the Muslim community is appealing to uncover where Islam originated and how it goes. This research is focused to see Islamization networks formed on indigenous lands in the southern coastal areas of the island of Seram by conducting the archaeological research that adopted survey method and oral history interviews to discover traces of the presence of Islam. This study found that Islamization in the southern coastal areas of the island of Seram, arised from the central region of Islam in the Maluku Islands; with another possibility that have been introduced from Java and the homeland of Islam, Arab and Persia. The study also found the formation process of political networks in the spread of Islam to get to the southern coastal areas of the island of Seram.Dalam sejarah Islamisasi di wilayah Pulau Seram Maluku sejauh ini, hanya menyebut Kerajaan Hoamoal sebagai pusat Islamisasi di wilayah tersebut. Meski demikian, terbentuknya negeri-negeri adat yang dihuni komunitas muslim, menarik untuk diungkap dari mana Islam berasal dan bagaimana perkembangannya. Penelitian ini difokuskan untuk melihat jaringan Islamisasi yang terbentuk pada negeri-negeri adat di wilayah pesisir selatan Pulau Seram. Melalui penelitian arkeologi, dengan metode survei serta wawancara untuk menelusuri sejarah lisan jejak kehadiran Islam. Penelitian ini menemukan bahwa Islamisasi di wilayah pesisir selatan Pulau Seram, berasal dari wilayah pusat kekuasaan Islam di Kepulauan Maluku, juga kemungkinan dari Jawa dan tanah asal Islam dari Arab dan Persia. Penelitian ini juga menemukan bagaimana terbentuknya jaringan politik dalam proses penyebaran Islam hingga sampai ke wilayah pesisir selatan Pulau Seram.